Pengetahuan dan Sikap Bidan Terhadap Penularan HIV/AIDS dalam Pelaksanaan Praktek Universal Precaution - Agung Budianto; Zahroh Shaluhiyah; Bagoes Widjanarko (Jurnal Promosi Kesehatan Indonesia, 2010)
Midwife’s attitude and knowledge to HIV/AIDS transmition in universal precaution practice;Health provider like a midwife is very high risk to infection HIV in delivery. And many casescan infection HIV because of occupational in their job. This Article aims finding in the year2009 about practice of universal precaution about prevention of infection of HIV by midwife tohelp delivery in Wanadadi Banjarnegara. This research was representative quantitative researchtype using cross sectional approach, with 64 active midwives as sample in Wanadadi. Samplewas representative totally population. Data collecting of research by using structure equated.Data analysis used univariate, bivariate and multivariate. Results to show that in general, manymidwives not obedient get in universal precaution in delivery practice that to high risk infectionof HIV/AIDS. Knowledge about HIV is the most influence (p-value = 0.001) than another variablelike as attitude to HIV (p-value = 0.026) and equipment (p value = 0.015) were significantlycorrelated to universal precaution practice delivery with midwife. It is recommended that from10 free variable related to practice universal precaution there 4 corresponding variable whileknowledge variable about HIV strongest its influence.Keyword: knowledge, attitude, HIV, AIDS